Tornar-se terapeuta: a prática da meditação na formação do psicólogo clínico de orientação fenomenológica - Rosmaninho, Marta Tolaini (2010)
The aim of this work is to understand in a phenomenological perspective, the contribution of the practice of Vipassana meditation for the development of the way of being present of the therapist. Considering that the trainning of the therapist goes beyond the acquisition of theoretical knowledge, which also includes several personal processes that contribute to the unique way to become a therapist, I retake in this dissertation to my personal journey as a therapist and practitioner of Vipassana meditation. In a phenomenological perspective I focused on the experiences of meditation in a process of immersion and distance, which allowed me to reflect and express the effects of meditation on my personal way of being a therapist. Based on the description of my experiences in meditation practice as well as on clinical vignettes, I point out how my way of being present with clients was helped by the practice of meditation. This work shows that trainning in psychotherapy is more than the learning of theorical knowledge, for it includes personal processes which contribute to one s becoming a therapist